Dentition of the Malaysian Lesser Mouse-deer (Tragulus javanicus) - Vidyadaran, M. K.; Sirimane, R. A.; Hilmi, M. (1981)
The dentition of twenty five lesser mouse-deer (Tragulus javanicus) is described. Comparisons with the dentition of the ox and the goat showed very few differences in the molars among these species. However, the incisors and the premolars showed many differences. The premolars of the lesser mouse-deer are more suited for piercing and chopping food rather than for chewing.